Pathways from family disadvantage via abusive parenting and caregiver mental health to adolescent health risks in South Africa - Meinck, F; Cluver, L; Orkin, F; Kuo, C; Sharma, A; Hensels, I; Sherr, L (Elsevier, 2016)
Purpose Adolescent health is a major concern in LMIC but little is known about its predictors. Family disadvantage and abusive parenting may be important factors associated with adolescent psychological, behavioral and physical health outcomes. This study, based in South Africa, aimed to develop an empirically-based theoretical model of relationships between family factors such as deprivation, illness and parenting and adolescent health outcomes. Methods Cross-sectional data were collected in 2009-2010 from 2477 adolescents (aged 10-17) and their caregivers using stratified random sampling in KwaZulu-Natal, South Africa. Participants reported on socio-demographics, psychological symptoms, parenting and physical health. Multivariate regressions were conducted, confirmatory factor analysis employed to identify measurement models and a structural equation model developed. Results The final model demonstrated that family disadvantage (caregiver AIDSillness and poverty) was associated with increased abusive parenting. Abusive parenting was in turn associated with higher adolescent health risks. Additionally, family disadvantage was directly associated with caregiver mental health distress which increased adolescent health risks. There was no direct effect of family disadvantage on adolescent health risks but indirect effects through caregiver mental health distress and abusive parenting were found. Conclusions Reducing family disadvantage and abusive parenting is essential in improving adolescent health in South Africa. Combination interventions could include poverty and violence reduction, access to health care, mental health services for caregivers and adolescents, and positive parenting support. Such combination packages can improve caregiver and child outcomes by reducing disadvantage and mitigating negative pathways from disadvantage among highly vulnerable families.